Ovarian thecoma: A very unusual cause of postmenopausal bleeding. Issue 3 (September 2021) - Arteaga, E; Valenzuela, F; Martinez, A; Huete, A; Aspee, M
We describe a 67-year-old woman with postmenopausal bleeding having ceased estrogen plus progestogen therapy nine months before. Transvaginal ultrasonography showed endometrial thickening with normal ovarian appearance. Hormonal studies revealed high estradiol and inhibin B levels but normal androgens and adrenal hormones. Magnetic resonance image demonstrated a 13-mm left ovarian tumour. Hysterectomy and bilateral salpingo-oophorectomy were performed, and the pathological study revealed an 8 mm ovarian thecoma. This case illustrates a very unusual cause of postmenopausal bleeding. We suggest a study protocol and discuss the differential diagnosis of this case.